(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
The 2003 Halloween storms (October 2931) were among the most intense geomagnetic disturbances of the 23rd solar cycle, significantly altering ionospheric conductivity, temperature, and electron density. These storms were triggered by powerful coronal mass ejections (CMEs) from the Sun, leading to severe space weather effects on Earth’s magnetosphere and ionosphere. The resulting geomagnetic activity caused strong auroral enhancements, disruptions in GPS and radio communications, and increased drag on low-Earth orbiting satellites. Understanding the ionospheric response to such extreme events is crucial for space weather prediction and lessen their effects on communication and navigation systems. The aim of this study is to investigate the altitude-dependent variations in ionospheric conductivity during geomagnetic storms, with a particular focus on anisotropies and their influence on ionospheric dynamics. Previous studies primarily focused on global-scale ionospheric disturbances but lacked high-resolution characterization of conductivity anisotropies at different altitudes. This study presents a detailed analysis of ionospheric parameters using data from the World Data Center for Geomagnetism, Kyoto, and the CCMC Instant Run System on the IRI model. Unlike prior investigations, this research examines altitude-dependent variations in conductivity, particularly the role of anisotropies during geomagnetic storms. Results show electron density peaking at 1.36 10 cm at 400 km, while electron temperature rises to 2,714 K at 1000 km. A key finding is the suppression of Hall conductivity at 100200 km, attributed to increased ion-neutral collisions and storm-driven neutral composition changes.